A Comparison of Patient and Provider Perspectives on an Electronic Health Record–Based Discharge Communication Tool: Survey Study - Dorothy Yingxuan Wang; Eliza Lai-Yi Wong; Annie Wai-Ling Cheung; Kam-Shing Tang; Eng-Kiong Yeoh (JMIR Aging)
Abstract BackgroundHospital discharge for older adult patients carries risks. Effective patient-provider communication is crucial for postacute care. Technology-based communication tools are promising in improving patient experience and outcomes. However, there is limited evidence comparing patient and provider user experiences on a large-scale basis, hindering the exploration of true patient-provider shared understanding. ObjectiveThis study aimed to evaluate an electronic health record–based discharge communication tool by examining and comparing patient and provider perspectives. MethodsThis study comprised a cross-sectional self-administered staff survey and a pre-post cross-sectional patient survey. Physicians, nurses, and older adult patients aged 65 years and older discharged from 4 public hospitals were included. Patient-provider comparison items focused on 3 aspects of the design quality of the tool (information clarity, adequacy, and usefulness) and overall satisfaction with the tool. In addition, patients’ experience of discharge information and their medication-taking behaviors before and after the program implementation were compared based on a validated local patient experience survey instrument. Providers’ perceived usefulness of this tool to their work and implementation intentions were measured based on the technology acceptance model to enhance understanding of their experiences by conducting structural equation modeling analysis. ResultsA total of 1375 and 2353 valid responses were received from providers and patients, respectively. Patients’ overall satisfaction with this communication tool is significantly higher than providers’, and patients rated the information clarity and usefulness presented by this tool higher as well (PPP ConclusionsA notable disparity exists between patients and health care providers. This may hinder the achievement of the tool’s benefits. Future research should aim for a comprehensive overview of implementation barriers and corresponding strategies to enhance staff performance and facilitate patient-provider shared understanding.